Butylated Hydroxytoluene (BHT) Protects SH-SY5Y Neuroblastoma Cells from Ferroptotic Cell Death: Insights from In Vitro and In Vivo Studies - Parisa Faraji; Astrid Borchert; Shahin Ahmadian; Hartmut Kuhn (MDPI AG, 2024)
Ferroptosis is a special kind of programmed cell death that has been implicated in the pathogenesis of a large number of human diseases. It involves dysregulated intracellular iron metabolism and uncontrolled lipid peroxidation, which together initiate intracellular ferroptotic signalling pathways leading to cellular suicide. Pharmacological interference with ferroptotic signal transduction may prevent cell death, and thus patients suffering from ferroptosis-related diseases may benefit from such treatment. Butylated hydroxytoluene (BHT) is an effective anti-oxidant that is frequently used in oil chemistry and in cosmetics to prevent free-radical-mediated lipid peroxidation. Since it functions as a radical scavenger, it has previously been reported to interfere with ferroptotic signalling. Here, we show that BHT prevents RSL3- and ML162-induced ferroptotic cell death in cultured human neuroblastoma cells (SH-SY5Y) in a dose-dependent manner. It prevents the RSL3-induced oxidation of membrane lipids and normalises the RSL3-induced inhibition of the intracellular catalytic activity of glutathione peroxidase 4. The systemic application of BHT in a rat Alzheimer's disease model prevented the upregulation of the expression of ferroptosis-related genes. Taken together, these data indicate that BHT interferes with ferroptotic signalling in cultured neuroblastoma cells and may prevent ferroptotic cell death in an animal Alzheimer's disease model.